Edukasi Gizi sebagai Upaya Peningkatan Pengetahuan Pencegahan Stunting pada Kader Posyandu dalam Program “Desa Emas: Percepatan Penurunan Stunting” - Auresa Caesarputriaulya Willmart; Fransisca Nimas Restu Krissandiani; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2024)
Background: One form of promotive and preventive efforts to accelerate the reduction of stunting is active role of posyandu cadres in carrying out nutrition counseling to mothers of toddlers to increase knowledge related to nutrition so as to achieve optimal public health status. Therefore, efforts are needed to increase the knowledge of posyandu cadres, one of which can be done through nutrition education. Objective: This study aims to provide nutrition education as an effort to increase posyandu cadres' knowledge regarding stunting prevention as a form of integrated community service in the "Golden Village: Accelerating Stunting Reduction" program in 2022. Methods: This study used the one group pre-test and post-test method. design with 13 posyandu cadres as respondents. Nutrition education is provided using interactive presentation methods and animated videos. Results: The results of the study showed that the average posyandu cadre’s knowledge score increased from 40.77 ± 9.5 before education to 41.54 ± 12.8 after education. The results of the study were analyzed using the paired T-test showing that the average score of knowledge of cadres before (40.77 ± 9.5) and after (41.54 ± 12.8) education did not increase significantly (p-value = 0.721). Conclusion: Nutrition education using interactive presentation methods and educational video exposure which was carried out for 60 minutes for posyandu cadres showed an increase in the level of knowledge before compared to after education. However, the increase in knowledge of posyandu cadres did not occur significantly. Thus, nutrition education using interactive presentation methods and animated videos is considered less effective in increasing the knowledge of posyandu cadres, so it is advisable to provide nutrition education using simulation techniques and practices which are carried out in stages in several meetings as an effort to increase the knowledge of posyandu cadres to get significant results.